Pattern of the head and the neck cancer in two geographically and socioeconomically different countries - Somayyeh Azimi; Hamed Mortazavi; Marc Tennant; Estie Kruger; Babak Rezaei; Jamileh B Taheri; Mohammad R Tarahhomi (Wolters Kluwer Medknow Publications, 2017)
Context: The differences in frequency of cancer among the less developed and the more developed regions continue to remain as an important problem for service planning and international action against cancers of the head and the neck. Aim: This study compares distribution of cancers of the head and the neck between two similar-sized populations from the west of Iran and Western Australia. Setting and Design: In this retrospective study, de-identified data were collected for a 10-year period from patients diagnosed with head and the neck cancers. Materials and Methods: Data were obtained from the Western Australia Cancer Registries and from major hospitals in the west of Iran. Age at diagnosis, sex, and site code were included in the data sheet. Descriptive analysis was used to describe the basic features, means (±standard deviation) were reported, and tests of significance were used as appropriate. Results: In Iran, cancer of the lip, followed by cancer of the major salivary gland, and cancer of the tongue were the three most frequent types of cancers, whereas in Australia, the most frequent types of cancer were cancer of the lip followed by cancers of the tongue and the tonsil. Distribution of malignancy by site among the patients belonging to different ages indicated that cancer of the lip was the most frequent cancer in both Iran and Australia, except among the patients belonging to the age group of 60-74 years in Iran, where cancer of the major salivary gland had the highest frequency. Both men and women were susceptible for cancers of the head and the neck in the age range of 60-74 years in Iran, whereas in Australia, it was more frequent among men belonging to the age range of 45-59 years and in women above the age of 75 years. Conclusion: This preliminary study defined differences in orofacial malignancy between Iran and Australia. Further studies in countries with different socioeconomic status are recommended.